Steel surface TiCrN, TiMoNcoatings structural phase state change features after low-energy alpha particles irradiation; IOP Conference Series: Materials Science and Engineering; Vol. 289 : Modern Technologies for Non-Destructive Testing - Kislitsin S. B.; Potekaev A. I .; Uglov V. V. Vladimir Vasilievich; Klopotov A. A.; Klopotov V. D. Vladimir Dmitrievich; Ivanov Yu. F. Yuriy Fedorovich; Parpiev A. T. (2018, 2018)
Title screen